2017
DOI: 10.1107/s2053230x17015436
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of domain movement in active-site mutants of porphobilinogen deaminase fromBacillus megaterium

Abstract: The enzyme porphobilinogen deaminase (PBGD) is one of the key enzymes in tetrapyrrole biosynthesis. It catalyses the formation of a linear tetrapyrrole from four molecules of the substrate porphobilinogen (PBG). It has a dipyrromethane cofactor (DPM) in the active site which is covalently linked to a conserved cysteine residue through a thioether bridge. The substrate molecules are linked to the cofactor in a stepwise head-to-tail manner during the reaction, which is catalysed by a conserved aspartate residue:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The missing coordinates of the residues 60-78 (part of the active-site loop and adjoining region) were modeled based on the structure of AtHMBS [PDB ID code 4HTG (10)] using Modeler 9v8 (22). The missing residues at the N-terminal (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the C-terminal (residues 358-361) were also modeled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The missing coordinates of the residues 60-78 (part of the active-site loop and adjoining region) were modeled based on the structure of AtHMBS [PDB ID code 4HTG (10)] using Modeler 9v8 (22). The missing residues at the N-terminal (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the C-terminal (residues 358-361) were also modeled.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of the purified Escherichia coli and human enzymes demonstrated the critical importance of a covalently bound dipyrromethane (DPM) cofactor and the occurrence of stable enzyme substrate complexes in the formation of HMB (4,(6)(7)(8). To date, the X-ray crystal structures of E. coli (9), Arabidopsis thaliana (10), Bacillus megaterium (11,12), and human (13,14) HMBS (hHMBS) with their DPM cofactors have been reported. The crystal structures of the hHMBS housekeeping isoform are available in the Protein Data Bank (PDB) under ID codes 3EQ1 (13) and 3ECR (14).…”
mentioning
confidence: 99%
“…PDB entries 5ov4, 5ov5 and 5ov6 are crystal structures that each involve a mutant of the catalytic aspartic acid (Asp82 in Bacillus megaterium numbering). Guo et al (2017) reported that 'the only mutant, D82E, which has the whole cofactor bound in a well ordered manner is catalytically active, while the other two (D82A and D82N) are not'.…”
Section: Commentary On the Role Of The Pdb Data Files In Structural And Functional Studies Of Hmbsmentioning
confidence: 99%
“…Before the widespread prevalence of Bacillus subtilis , B. megaterium had been widely used in biochemical research due to its extensive metabolic capacity and physical properties conducive to biotechnology applications ( Hitchins et al, 1968 ; Elmerich and Aubert, 1971 ). The strain is a commercially available, nonpathogenic host, which has been used to produce various enzymes, such as penicillin amidase, amylase, amino acid dehydrogenase, and glucose dehydrogenase, as well as to produce recombinant proteins ( Lammers et al, 2004 ; Malten et al, 2005 ; Biedendieck et al, 2011 ; Grage et al, 2017 ; Guo et al, 2017 ). Moreover, B. megaterium can synthesize vitamin B 12 through an oxygen-independent adenosylcobalamin pathway ( Eppinger et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%